CODE MIXING IN HITAM PUTIH TALK SHOW - KhalidaHaris and Sumarsih (LINGUISTICA, 2015)
The study deals with the code mixing in HitamPutih Talk Show Program on Trans 7.The objectives of study were to identify the types of code mixing used, to find out themost dominant type of code mixing used, and to describe the reasons of the codemixing used in the talk show. The data consisted of three episodes of HitamPutihTalk Show on April – October 2014. The findings show that there were 116insertions (32, 86%), 149 alternations (42, 2%), 88 congruent lexicalizations (24,92%). The most dominant type of code mixing was alternation becausethe host oftenclarified the guest’s statement to make the audience more understand what the guestsaid before, so they combined their speech with other language.